Rugby Union and Globalization - Harris, J. author. aut Link
XVI, 168 p.
Keywords: In 1995 rugby union finally became a professional sport following more than a century as an amateur game. This book offers a critical analysis of the sport in the professional era and assesses the relationship between the local and the global in contemporary rugby union.